Pelatihan dan pendampingan pembuatan mie bakso dari tepung sagu sebagai upaya pengembangan ekonomi jemaat pada ibu-ibu persekutuan wanita jemaat GKI Maranatha Kampung Yoboi, Klasis GKI Sentani, Kabupaten Jayapura: Training and assistance in making meatball noodles from sago flour as an effort to develop the congregation's economy for mothers of the GKI Maranatha Congregational Women's Fellowship, Yoboi Village, GKI Sentani Klasis, Jayapura Regency - Cleopatriza T. F. Ruhulessin (Fakultas Peternakan Universitas Papua, 2023)
ABSTRACT The GKI Inri Pulende congregation is one of the congregations on the shores of Lake Sentani. The use of sago as a local commodity for the economic development of families and congregations is one of the problems currently being faced. Sago is the staple food of the Sentani people, which is processed into a variety of foods in order to maintain this local food for the welfare of the people. One of the resistances carried out to maintain the religious and economic cultural values ​​of this local commodity is training and mentoring in the use of sago for the Women's Fellowship of the GKI Inri Pulende Congregation. The production of meatball noodles from sago flour is the right choice to deal with various food traps that can weaken the existence of sago as a cultural identity for the Sentani people in the modernization era. Meatball noodles from sago flour as traditional food with high cultural taste is very popular among various groups of village people. Two targets to be achieved from this activity are: Production of meatball noodles from sago flour as a substitute for ordinary flour and Creating a sago meatball stall business to improve the economy of families and congregations. Women who were trained in the process of making sago flour into the basic ingredient for making noodles actively participated in the activity until the end. They have been able to make meatball noodles from sago flour and tilapia fish meatballs with basic ingredients from sago flour. Keywords: Congregational economy; Making meatball noodles; Sago flour; Training ABSTRAK Jemaat GKI Inri Pulende merupakan salah satu jemaat yang berada di pesisir danau Sentani. Pemanfaatan sagu sebagai komoditas lokal bagi pengembangan ekonomi keluarga dan jemaat merupakan salah satu permasalahan yang dihadapi saat ini. Sagu menjadi makanan pokok masyarakat Sentani, yang diolah menjadi aneka ragam pangan guna mempertahankan pangan lokal ini demi kesejahteraan masyarakat. Salah satu resistensi yang dilakukan untuk mempertahankan nilai kultur religi dan ekonomi dari komuditas local ini adalah pelatihan dan pendampingan pemanfaatan sagu kepada Persekutuan Wanita Jemaat GKI Inri Pulende. Produksi mie bakso dari tepung sagu, menjadi pilihan yang tepat untuk menghadapi berbagai jebakan-jebakan pangan yang dapat memperlemah eksistensi sagu sebagai identitas kultur orang Sentani di era modernisasi. Mie bakso dari tepung sagu sebagai pangan tradisional yang bercita rasa budaya tinggi sangat digemari oleh berbagai kalangan masyarakat kampung. Ada dua target yang ingin dicapai dari kegiatan ini adalah: a. Produksi mie bakso dari tepung sagu penganti tepung biasa, b. Membuat usaha warung bakso sagu untuk meningkatkan ekonomi keluarga dan jemaat. Ibu-Ibu yang dilatih proses pembuatan tepung sagu menjadi bahan dasar pembuatan mie aktif mengikuti sampai dengan akhir dari kegiatan. Mereka sudah dapat membuat mie bakso dari tepung sagu dan bakso ikan mujair dengan bahan dasar tepung sagu. Kata Kunci: Ekonomi jemaat; Pelatihan; Pembuatan mie bakso; Tepung sagu